Compact solid-state optical phased array beam scanners based on polymeric photonic integrated circuits - Sung-Moon Kim (Nature Portfolio, 2021)
Abstract Optical phased array (OPA) devices are being actively investigated to develop compact solid-state beam scanners, which are essential in fields such as LiDAR, free-space optical links, biophotonics, etc. Based on the unique nature of perfluorinated polymers, we propose a polymer waveguide OPA with the advantages of low driving power and high optical throughput. Unlike silicon photonic OPAs, the polymer OPAs enable sustainable phase distribution control during beam scanning, which reduces the burden of beamforming. Moreover, by incorporating a tunable wavelength laser comprising a polymer waveguide Bragg reflector, two-dimensional beam scanning is demonstrated, which facilitates the development of laser-integrated polymeric OPA beam scanners.